STRATEGIES AND CHALLENGES: MADRASAH PRINCIPAL LEADERSHIP IN ENHANCING TEACHER PERFORMANCE FOR ACADEMIC EXCELLENCE - Rifai, Moh; Zahro, Siti Fatimatus (Managere: Indonesian Journal of Educational Management, 2023)
One of the interesting problems to study in the world of education regarding human resources is teacher performance. A nation is developed if it has quality resources. This research was conducted to determine the leadership of Madrasah Heads in Improving Teacher Performance at Madrasah Aliyah Nurul Jadid. The research methodology uses a qualitative approach with a case study type of research. Data sources were obtained through observation, interviews and documentation. The data analysis technique goes through three stages, namely data reduction, data display (data presentation) and data conclusion drawing/verification. The validity of the data in this research uses source triangulation and technical triangulation. The results of this research are 1) Leadership carried out by the head of the madrasah, namely providing motivation and supervision and support related to teacher duties, involving teachers to take part in training and implementing rewards and punishments to their employees for better performance. 2) The madrasa head's leadership style in improving teacher performance at Madrasah Aliyah Nurul Jadid is a democratic style through discussion or deliberation, openness, giving freedom to subordinates and giving subordinates the opportunity to provide critical suggestions. 3) The principal's obstacles to improving teacher performance are still a lack of facilities and infrastructure, teacher indiscipline both in lesson planning and attendance. And they are less enthusiastic about teaching their students.